Analyzing the impact of holistic building design on the process of lifecycle management of building structures - Ahsan Waqar; Khaled A Alrasheed; Abdul Mateen Khan; Hamad Almujibah; Omrane Benjeddou (Scientific Reports)
Abstract This research examines how Holistic Building Design (HBD) affects Lifecycle Management of Building Structures in the ever-changing construction market. HBD includes adaptability, environmental sustainability, maintenance, and disaster preparation. It is a key idea in the present boom in resilient and sustainable building techniques. A surprising dearth of quantitative empirical research on HBD’s impact on LMBS considering the field’s growing importance. This study uses a quantitative method to explore the relationship between essential HBD components and LMBS outcomes especially Extended Service Life (ESL) and Optimized Performance and Value (OPV) are critical factors to address this information gap. The quantitative study polled 171 construction industry professionals and utilized Structural Equation Modelling to examine the data. This approach was selected for its ability to explore complex relationships between variables and constructs. HBD components Adaptability and Retrofitting (AAR), Environmental Considerations and Sustainability (ECS), Maintenance and Inspection Programs (MIP), and Resilience and Disaster Preparedness (RDP) profoundly influenced the Enhanced Service Life (ESL) and Optimized Performance and Value (OPV) elements of LMBS. Building adaptation and retrofitting, maintenance and inspection programs, and other activities increased building value and lifespan. These findings have major theoretical and practical implications. The work potentially fills a research gap by providing actual evidence on HBD-LMBS linkages. Practically, the results advise construction industry specialists to use HBD ideas for sustainable building management. Finally, our work illuminates the vital roles of HBD components in LMBS and paves the way for ecologically friendly building approaches.